Inhibition of cell wall-associated enzymes in vitro and in vivo with sugar analogs. - Nagahashi, G; Tu, S; Fleet, G; Namgoong, S (1990)
Sugar analogs were used to study the inhibition of cell wall-associated glycosidases in vitro and in vivo. For in vitro characterization, cell walls were highly purified from corn (Zea mays L.) root cortical cells and methods were developed to assay enzyme activity in situ. Inhibitor dependence curves, mode of inhibition, and specificity were determined for three sugar analogs. At low concentrations of castanospermine (CAS), 2-acetamido-1,5-imino-1,2,5-trideoxy-d-glucitol, and swainsonine, these inhibitors showed competitive inhibition kinetics with beta-glucosidase, beta-GIcNAcase, and alpha-mannosidase, respectively. Swainsonine specifically inhibited alpha-mannosidase activity, and 2-acetamido-1,5-imino-1,2,5-trideoxy-d-glucitol specifically inhibited beta-N-acetyl-hexosamindase activity. However, CAS inhibited a broad spectrum of cell wall-associated enzymes. When the sugar analogs were applied to 2 day old corn seedlings, only CAS caused considerable changes in root growth and development. To ensure that the concentration of inhibitors used in vitro also inhibited enzyme activity in vivo, an in vivo method for measuring cell wall-associated activity was devised.